2010
DOI: 10.1128/jvi.01961-09
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Type 5 Utilizes Alternative Translation Initiation To Encode a Small Rep40-Like Protein

Abstract: Alternative splicing of adeno-associated virus type 2 (AAV2) P19-generated pre-mRNAs generates the small Rep proteins Rep52 and Rep40, which differ in their carboxyl termini. Both proteins are required for optimal packaging of AAV2 genomes. AAV5 Rep-encoding P19-generated transcripts are primarily polyadenylated within the central intron and not efficiently spliced; however, surprisingly, AAV5 was found to generate high levels of a Rep40-like protein. The AAV5 Rep40-like protein was generated by internal initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 15 publications
(27 reference statements)
0
14
0
Order By: Relevance
“…Because AAV5 P7 and P19 RNAs are not spliced, they were predicted to encode only Rep78 and Rep52 (Fig. 1); however, we have shown that while an AAV5 Rep68 protein was absent, as expected, AAV5 encodes an abundant Rep40-like protein from an in-frame internal initiation AUG 150 nucleotides (nt) downstream of the Rep52 initiator (7). That AAV5 uses another genetic mechanism to generate a Rep40-like protein is consistent with it playing an essential role during infection.…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…Because AAV5 P7 and P19 RNAs are not spliced, they were predicted to encode only Rep78 and Rep52 (Fig. 1); however, we have shown that while an AAV5 Rep68 protein was absent, as expected, AAV5 encodes an abundant Rep40-like protein from an in-frame internal initiation AUG 150 nucleotides (nt) downstream of the Rep52 initiator (7). That AAV5 uses another genetic mechanism to generate a Rep40-like protein is consistent with it playing an essential role during infection.…”
mentioning
confidence: 51%
“…2C). We have previously shown that when the 150-nt region between the two AAV5 small-Rep AUGs (here termed AUG1 and AUG2, respectively) was replaced with the analogous region from AAV2, the downstream AAV5 AUG (AUG2) was not used at detectable levels (7). As can be seen in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, AAV-5 transcription and RNA processing is divergent, involving alternative polyadenylation and distance-dependent RNA processing (8)(9)(10). Several unique transcripts are created from the AAV-5 genome, such as functional truncated versions of the viral replication proteins (11)(12)(13). In addition, in contrast to other serotypes, transcription of AAV-5 capsid proteins does not require Rep expression (14).…”
mentioning
confidence: 99%